Banking Regulation: A Systemic View on Capital Adequacy, Financial Systems and the Regulatory Process - Hans-Peter Burghof (Credit and Capital Markets – Kredit und Kapital, 2020)
In a comment for the Finance Committee of the Deutscher Bundestag on the finalization of Basel III, I scrutinize the debate on the costs of bank equity, look at the incentive effects and potential distortions provoked by the actual regulatory regimes, and finally describe banks' regulation as a hysteretic process that creates detrimental phases of under- und overregulation. With regard to the first topic, I find strong arguments in the theory of financial intermediation that, in contradiction to the reasoning in the influential paper of Admati et~al. (2010), bank equity is indeed costly and excessive capital requirements would hamper the efficiency of the banking system. Furthermore, I identify several incentive effects of today's regulatory setting that lead to a more homogenous banking system with larger banks. This development could have negative effect on efficiency, in particular with regard to special needs of the German economy. And although the individual banks might be safer under the new regime, the evolving structure will probably contain a higher systemic risk.
Keywords: G21; G28; 330; Bank Regulation; Costs of Regulatory Capital; Banking Systems